A new symmetric solid-oxide fuel cell with La0.8Sr0.2Sc0.2Mn0.8O3-d perovskite oxide as both the anode and cathode - Zheng, Y.; Zhang, C.; Ran, R.; Cai, R.; Shao, Zongping; Farrusseng, D. (Pergamon Press, 2009)
A novel perovskite-type La0.8Sr0.2Sc0.2Mn0.8O3 (LSSM) oxide was synthesized and evaluated as the electrode material of a symmetric solid-oxide fuel cell. Characterization was done by electrical conductivity, crystal structure stability, redox stability, catalytic activity for methane oxidation and oxygen electro-reduction. LSSM shows greater electrical conductivity than the typical La0.8Sr0.2Cr0.5Mn0.5O3 (LSCM) perovskite oxide under both anode and cathode operating conditions. It also shows excellent chemical and structural stability due to the backbone effect of Sc3+ for the perovskite lattice structure. A symmetric electrolyte-supported cell with 0.3 mm thick scandium-stabilized zirconia electrolyte and LSSM as cathode and anode shows peak power densities of 310 and 130 mW cm2 at 900 °C, respectively, when operating on wet H2 and wet CH4. Stable performance is demonstrated. © 2008 Acta Materialia Inc.